Biodegradation of Textile Effluent using Plants and Algae - Dr.Krishnakumari, (International Journal of Scientific Research and Management (IJSRM), 2022)
Increasing globalization causes different environmental pollution. Out of pollution caused by various industries such as textile, dyeing and printing, paper, pulp, plastics, food, cosmetics and pharmaceuticals. Textile effluent causes one of the major environmental problems. The effluent from textile industries poses a threat to the environment, due to the presence of various pollutants. Different types of dyes used in the textile industry usually have a synthetic origin and complex aromatic molecular structures which make them more stable and more difficult to degrade. The complex textile effluent can be biodegraded by algae (bioremediation) and various plants (phyto remediation) reduce the complex pollutants into detoxified smaller compounds.